IDNLearn.com connects you with experts who provide accurate and reliable answers. Join our interactive community and get comprehensive, reliable answers to all your questions.

Find the first difference given the second and third term.

Second term: [tex]3a + 5[/tex]
Third term: [tex]8a - 3[/tex]

The first difference is [tex]\square[/tex]


Sagot :

To find the 1st difference between the given terms in the sequence, we can follow these steps:

1. First, plug in the value of [tex]\( a = 1 \)[/tex] into both the second and third term expressions:

- The second term is given by [tex]\( 3a + 5 \)[/tex]:
[tex]\[ a_2 = 3(1) + 5 = 3 + 5 = 8 \][/tex]

- The third term is given by [tex]\( 8a - 3 \)[/tex]:
[tex]\[ a_3 = 8(1) - 3 = 8 - 3 = 5 \][/tex]

2. Next, calculate the 1st difference, which is the difference between the third term and the second term:
[tex]\[ \text{1st Difference} = a_3 - a_2 = 5 - 8 \][/tex]

3. Simplify the result:
[tex]\[ \text{1st Difference} = -3 \][/tex]

Therefore, the 1st difference is [tex]\( -3 \)[/tex].